+0  
 
0
197
1
avatar+604 

If $x^2 + bx + b + 3 = 0$ has roots of the form $\frac{-b \pm \sqrt{5}}{2}$, where $b > 0 $, then $b = m+\sqrt{n}$ for positive integers $m,n$. Find $m + n$.

gueesstt  May 6, 2018
 #1
avatar+20009 
+2

If $x^2 + bx + b + 3 = 0$ has roots of the form $\frac{-b \pm \sqrt{5}}{2}$, where $b > 0 $,

then $b = m+\sqrt{n}$ for positive integers $m,n$. Find $m + n$.

 

\(\begin{array}{|rcll|} \hline \left( x - \frac{-b +\sqrt{5}}{2} \right)\left( x - \frac{-b - \sqrt{5}}{2} \right) &=& x^2+bx+b+3 \\ \left( x + \frac{b}{2} -\frac{\sqrt{5}}{2} \right)\left( x + \frac{b}{2} +\frac{\sqrt{5}}{2} \right) &=& x^2+bx+b+3 \\ \left( ( x + \frac{b}{2}) -\frac{\sqrt{5}}{2} \right)\left( (x + \frac{b}{2}) +\frac{\sqrt{5}}{2} \right) &=& x^2+bx+b+3 \\ \left( x + \frac{b}{2} \right)^2- \left(\frac{\sqrt{5}}{2} \right)^2 &=& x^2+bx+b+3 \\ x^2+xb+\frac{b^2}{4}- \frac{5}{4} &=& x^2+bx+b+3 \\ \frac{b^2}{4}- \frac{5}{4} &=& b+3 \\ \frac{b^2}{4}-b - \frac{5}{4} -3 &=& 0 \quad & | \quad \cdot 4 \\ b^2-4b - 5 -12 &=& 0 \\ b^2-4b - 17 &=& 0 \\\\ b &=& \frac{4\pm \sqrt{16-4\cdot(-17)}}{2} \\ &=& \frac{4\pm \sqrt{16+68}}{2} \\ &=& \frac{4\pm \sqrt{84}}{2} \\ &=&2\pm \frac{\sqrt{84}}{2} \\ &=&2\pm \sqrt{\frac{84}{4}} \\ &=&2\pm \sqrt{21} \quad & | \quad b>0\ !\\\\ \mathbf{b} & \mathbf{=} & \mathbf{2+\sqrt{21} } \\ b &=& m+\sqrt{n} \quad & | \quad m = 2 \text{ and } n = 21 \\ \mathbf{m+n} &\mathbf{=}& \mathbf{2+21=23} \\ \hline \end{array}\)

 

laugh

heureka  May 7, 2018

19 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.